A South African perspective on user-created content in cloud computing: a copyright conundrum - Hauman, Mignon (University of the Free State, 2014)
English: The term “cloud computing”, i.e. “the cloud”, is used to describe a virtual platform in cyberspace from and to which a user can process store data that is literary, musical, artistic or informative in nature, and which is accessible via an Internet connection. The cloud therefore functions as virtual container that holds, processes and distributes all forms of copyrighted content, and which operates outside the confines of recognised territorial boundaries. The cloud is not only distributive but participatory. It fosters a “cut and paste” culture by allowing users to access, store, remix and create content. The cloud promotes user-created content, a term that encompasses and insurmountable range of actions by users with respect to cloud content available on the World Wide Web. Prominent scholars have devised a taxonomy for the categorisation and classification of cloud content to some degree, but there is wide spread acknowledgement that the nature of the cloud cannot be confined to a decisive definition, nor its content exact parameters. The inexact nature of the cloud and its content poses challenges for copyright law, a regime that is premised on a distinctive subject matter, confined to territorial boundaries and aimed at identifiable parties with respect to its application. In the cloud traditional copyright law seems wholly inadequate to provide regulation on matters of infringement, fair dealing and copyright recognition. Moreover, the inadequacy of the regime for cloud application threatens to weaken its validity as a mechanism that aims to promote the innovation of works for the benefit of the general public. If copyright law is to remain a valid instrument for the regulation of user-created content in cloud computing there is a definitive need to re-evaluate, revise and expand some of the regulatory devices thereof to accommodate the expectations and interests of cloud users. Finding a means to balance the rights of copyright holders against the interests of the general public has never been more critical, and policy makers have become ever aware of the need to develop a robust copyright regime for cloud application. Accordingly, this study aims to investigate the insufficiency of South African copyright law to adequately regulate the conduct of users who can acquire, remix, upload, derive and share vast amounts of copyrighted works via the Internet. The purpose of this study is to analyse potential developments in copyright law for cloud application in order to gain insight on the regulation and adjudication of user-created content within a South African context.

Afrikaans: Die term “cloud computing” of “the cloud” verwys letterlik na ‘n konsep waar rekenaars op ‘n virtuele platform in die kuberruim funksioneer, vandaar die verwysing na ‘n wolk in die lug (daar sal deurgaans verwys word hierna as die cloud). Van hierdie platform is dit dan moontlik vir rekenaargebruikers om data te stoor en te verwerk wat literêr, musikaal of artistiek van aard kan wees. Hierdie inligting is toeganklik via die Internet. Hierdie cloud funksioneer dus as ‘n virtuele stoor wat alle vorme van outeursregwerke kan stoor en vanwaar dit verwerk en versprei kan word buite erkende geografiese grense. Die cloud het nie net ‘n verspreidingsfunksie nie, maar moedig deelname aan tussen verskillende gebruikers deurdat dit ‘n kopieer-en-plak kultuur (“copy and paste culture”) daarstel. Gebruikers kan inhoud bekom, stoor, skep en herskep. Gebruiker-gegenereerde inhoud (“usercreated content”) word dus daardeur bevorder en sluit ‘n magdom van handelinge van gebruikers op die Internet in. Kenners het tot ‘n sekere mate terminologie ontwikkel vir die kategorisering en klassifikasie van die inhoud van die cloud, maar daar is ooreenstemming dat die aard van die cloud en die inhoud daarvan sodanig is dat dit nie beperk kan word nie. Hierdie onbepaaldheid bring sekere uitdagings mee vir outeursreg wat op ‘n eiesoortige vakinhoud binne vasgestelde grense gebaseer is en wat van toepassing is op identifiseerbare partye. Tradisionele outeursreg blyk ontoereikend te wees ten opsigte van outeursreginbreukmaking, billike gebruik en outeursregerkenning in die cloud. Hierdie ontoereikenheid kan tot gevolg hê dat die geldigheid van die cloud as meganisme wat die skep van outeursregwerke tot voordeel van die algemene publiek bevorder in gedrang kan kom. Die voortbestaan van outeursreg as geldige instrument om gebruiker-gegenereerde inhoud in die cloud te reguleer noodsaak die herevaluering, hersiening en uitbreiding daarvan om aan die verwagtinge van die cloud se gebruikers te voldoen en na hulle belange om te sien. Om ‘n balans te vind tussen die belange van outeursregreghebbendes en die algemene publiek was nog nooit van groter belang nie en beleidsmakers is bewus van die behoefte aan ‘n behoorlike outeursregbestel vir toepassings in die cloud. Hierdie studie beoog gevolglik om die ontoereikendheid van die Suid- Afrikaanse outeursreg te ondersoek om sodoende die optrede van gebruikers in die cloud te reguleer wat verskeie outeursregwerke op die Internet kan bekom, herrangskik, oplaai, aflaai en deel. Die doel van hierdie studie is om potensiële ontwikkelings in outeursreg vir toepassing in die cloud te analiseer om sodoende insig te kry oor die regulering en beoordeling van gebruiker-gegenereerde inhoud binne ‘n Suid-Afrikaanse konteks.
Keywords: Dissertation (LL.M (Mercantile Law))--University of the Free State, 2014; Cloud computing; Information technology; Copyright; Copyright infringement